RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN DATA IKM PADA DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA PALU BERBASIS WEB - Ardiansyah, Rizka; Rahim, Mohammad Arham (ScientiCO : Computer Science and Informatics Journal, 2019)
Small Micro and Medium Enterprise (IKM) is an industry that operates on a small or medium-scale. Palu city Trade and Industry department has a lot of the IKM data that are manually archived using a large folder and classified according to the year of making the permit or known as the Industrial Business License (SIUI). Aside from being archived manually, the IKM data are also archived electronically using Microsoft Excel. Employees who play a role in managing the IKM data has difficulty in term of searching and filtering process the IKM data for data distribution to the public, besides the number of IKM data is very large and continues to grow every year. IKM data is stored through excel files have a problem against computer viruses, which can make it become corrupt. Related parties from the office expect a system that can manage this IKM data safely, easy to operate (user-friendly), has a better interface (user experience) and fast in carrying out the data distribution process. Our proposed system has managed to run well and as expected in managing data and resolving what happened to the previous conventional method, which is about the distribution and also the safety of SMI data.